Roles and positions of Malay and Non-Malay children's songs in imparting local wisdom among Malaysian families - Abdul Latif @ Bapoo, Lilisuriani; Johari, Arina; Kama, Nonglaksana (Prince of Songkla University, Thailand, 2023)
Children's songs have been used for a long time to educate and persuade children to act in the manner expected by the society they are in. With numerous children’s songs in different languages being made available on the internet, the relevance, and roles of Malay and non- Malay children’s songs in Malaysian families must be explored. This qualitative study aimed to explore the willingness and reasons for Malaysian adults to play traditional Malay, modern Malay, and non-Malay children’s songs to their children. Perceptions of adults with different educational and economic backgrounds on the use of traditional Malay, modern Malay, and non-Malay children’s songs were obtained through a survey with closed and open-ended questions. Findings show that their reasons for playing Malay and non-Malay songs are similar among the respondents despite their different educational and economic backgrounds. Imparting local wisdom namely morals and values, however, is not the main reason for playing the children’s songs. Appreciation and use of Malay children’s songs also have a different purpose than non- Malay songs. It is suggested that serious efforts be made for more Malay children’s songs with community-based knowledge and cultural traditions to be produced for young children to learn and preserve.